Implementasi Pajak Pertambahan Nilai (PPN) atas Subsidi Liquefied Petroleum Gas (LPG) - Dwi Hariyani; Dwi Orbaningsih; Djuni Farhan (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2020)
In the VAT Act taxable entrepreneurs have the obligation to calculate, calculate, deposit and report using the VAT Period VAT. The implementation must be fulfilled by taxpayers as a form of compliance and compliance with the Taxation Law. At present the taxable entrepreneur (agent) of 3 kg LPG cylinders, especially Malang Raya, is in the midst of an issue related to the debt owed and the non-payment of VAT on delivery. The purpose of this study is to evaluate in detail the facts or phenomena related to the implementation of VAT on subsidies for 3 kg LPG cylinders applied to PT. Gunawan Migas and PT. Lancar Putra Jaya in accordance with the VAT Act. Data collection techniques used were observation, interviews and documentation. This research is a case study research with descriptive analysis technique with a qualitative approach. The results of the study are: a) Differences in the implementation of VAT applied at PT. Gunawan Migas and PT. Lancar Putra Jaya. b) Differences of opinion between taxpayers, tax authorities and practitioners in the field of taxation between VAT payable and VAT unpaid for submission. c) Taxpayers consider that the tax authorities only pursue the budget function compared to the regularend function. This research is important to be conducted as a study material for the Government and the Tax Service Office (KPP) to follow up on policies related to the regulation of subsidized LPG 3 kg cylinders. Keywords: Liquefied Petroleum Gas, VAT, Subsidies